Penyebab Dan Dampak Kebijakan Mortalitas Terhadap Pertumbuhan Penduduk - Bonaraja Purba; Muhammad Nazly Azra’I; Putri Wulan Anjelina Waruwu; Yoga Erguna Sitepu (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Death or mortality is one of the three components of the demographic process that influences population structure, the other two components are birth (fertility) and population mobility. The purpose of this study was to determine the causes of mortality on population growth and to determine the relationship between mortality and population growth. This research is a study of the dynamics of mortality in Indonesia in the past and future projections based on data from UN publications and the Census from BPS Indonesia. This research based on the object is a survey research with quantitative methods for analysis. Meanwhile, based on the existence of the population, this study uses a sampling method. This research also shows that mortality indicators in Indonesia continue to increase each period. The crude death rate in Indonesia shows a quite drastic decline. This means that the degree of health in Indonesia shows improvement in each period.